2000
DOI: 10.1021/ma991303k
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Kink Bands and Tilt Boundaries in Block Copolymers at Large Shear Strains

Abstract: The evolution of kink bands and kink band boundaries in a prealigned poly(styrene-bethylene propylene) lamellar diblock copolymer was investigated by applying steady shear at strains in the range of 1-10 strain units. Boundary morphologies were characterized using transmission electron microscopy. As the shear strain increases, both the kink bands and the lamellae within the kink bands rotate continuously toward the shearing direction, leading to a decrease in the tilt boundary angle and the kink band boundary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
53
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(57 citation statements)
references
References 19 publications
3
53
1
Order By: Relevance
“…In the TGB, on the other hand, the plane is parallel to the boundary surface. The KGB of block copolymers has been intensively studied, both experimentally [6,[8][9][10] and theoretically. [11] Thomas et al proposed the doubly periodic morphology approximating Scherk's first surface as a model for the TGB simply due to the minimization of the surface area, [12] which was later confirmed experimentally by Jinnai et al [13] In contrast to the KGB, there are only a few experimental studies concerning the structure of TGBs in the literature [6,7] and, to our best knowledge, there are no study dealing with the grain boundaries in the cylinder-forming block copolymers.…”
Section: Introductionmentioning
confidence: 99%
“…In the TGB, on the other hand, the plane is parallel to the boundary surface. The KGB of block copolymers has been intensively studied, both experimentally [6,[8][9][10] and theoretically. [11] Thomas et al proposed the doubly periodic morphology approximating Scherk's first surface as a model for the TGB simply due to the minimization of the surface area, [12] which was later confirmed experimentally by Jinnai et al [13] In contrast to the KGB, there are only a few experimental studies concerning the structure of TGBs in the literature [6,7] and, to our best knowledge, there are no study dealing with the grain boundaries in the cylinder-forming block copolymers.…”
Section: Introductionmentioning
confidence: 99%
“…The basic phenomenology of GB structures in BCP materials was first discussed by Gido and Thomas who classified and evaluated the various GB types associated with tilt and twist deformations of lamellar BCPs [6][7][8][9]. Subsequent experimental studies revealed the relevance of process parameters (such as the application of shear fields), molecular architecture, and composition on GB formation as well as the implications of GB defects on, for example, the permeability of BCP materials [10][11][12][13][14][15][16][17].Despite the abundance of GB defects and their demonstrated relevance on the physical properties of BCP materials, very little is known about the governing parameters that determine the formation of the various types of GB structures in BCPs or the evolution of GB structures during, for example, thermal annealing. One parameter that is of particular interest is the energy penalty associated with GB formation as it provides insight into both the mechanism and driving force of grain coarsening during annealing.…”
mentioning
confidence: 99%
“…The basic phenomenology of GB structures in BCP materials was first discussed by Gido and Thomas who classified and evaluated the various GB types associated with tilt and twist deformations of lamellar BCPs [6][7][8][9]. Subsequent experimental studies revealed the relevance of process parameters (such as the application of shear fields), molecular architecture, and composition on GB formation as well as the implications of GB defects on, for example, the permeability of BCP materials [10][11][12][13][14][15][16][17].…”
mentioning
confidence: 99%
“…It depends on the rate of shear and molecular weight, as was shown in an experimental study with polystyrene-b-pol(ethylenepropylene) copolymers [133] and also predicted theoretically [134]. The elastic distortion of chains in lamellae domains is often reflected as kink bands and tilting [135].…”
Section: Steady Shear Flows Of Ordered Diblocksmentioning
confidence: 70%